Association Between DNA Methylation of MTHFR and Diabetic Kidney Disease - Guoxiong Deng; Ziyi Feng; Xiaomu Kong; Peng Gao; Yongwei Jiang; Yi Liu; Meimei Zhao; Liang Ma (Journal of Diabetes Research)
Conclusion: Methylation of the MTHFR gene Exon 2 is a protective factor for DKD and may contribute to its onset and progression through its influence on HCY levels. These findings highlight the potential of MTHFR methylation as a biomarker for DKD.